2003
DOI: 10.1073/pnas.0630309100
|View full text |Cite
|
Sign up to set email alerts
|

Close identity of a pressure-stabilized intermediate with a kinetic intermediate in protein folding

Abstract: U biquitin, consisting of only 76 amino acid residues (8.6 kDa) with no disulfide bonds, is a signaling protein for an ATP-dependent protein degradation but also for other cellular processes (1). The basic folded structure of ubiquitin has been determined by X-ray crystallography (2) and NMR analysis (3-5). The ubiquitin fold, consisting of a four-stranded, antiparallel ␤-sheet and two short helices, is widely found in many proteins (6). Our previous NMR investigation, carried out on uniformly 15 N-labeled ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
122
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 32 publications
(33 reference statements)
4
122
0
1
Order By: Relevance
“…The structure is likely to be similar to that of the locally disordered conformer detected at high pressure (3.7 kbar and 0°C). 4 However, they did not report full unfolding of ubiquitin by this method.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The structure is likely to be similar to that of the locally disordered conformer detected at high pressure (3.7 kbar and 0°C). 4 However, they did not report full unfolding of ubiquitin by this method.…”
Section: Introductionmentioning
confidence: 97%
“…E-mail: akasaka@waka.kindai.ac.jp recognition. 4,5 Thus, the study of a conformational fluctuation of ubiquitin in a wider perspective is useful for delineating the molecular mechanism of its function.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin has no prosthetic groups or disulfide bonds, is highly soluble, and is thermostable (T M > 360 K) (27)(28), making it an ideal target for experimental folding studies. The N and C termini form consecutive strands in the β sheet and are in close contact, a common feature in two-state folders (29); indeed, early investigations established that ubiquitin folds on the millisecond timescale with an apparent two-state behavior (30)(31)(32)(33), but later studies suggested that additional on-or off-pathway intermediates may be populated depending on the experimental conditions (34)(35)(36)(37)(38)(39)(40)(41)(42). A protein engineering Φ-value analysis of ubiquitin folding is consistent with a transition state ensemble (TSE) characterized by a well-defined folding nucleus localized in the N-terminal region of the protein and encompassing the helix and first two β strands (43,44).…”
mentioning
confidence: 99%
“…Thus, water can be kept liquid down to 251 K at a pressure of 2.07 kbar (3). Pressure-assisted cold denaturation has been followed for ubiquitin (15)(16)(17), using high-pressure quartz NMR tubes. The analysis of chemical shift data, resonance intensities, and 15 N relaxation showed that the pressure-assisted cold unfolding of ubiquitin is not a simple two-state process, but that several intermediates exist at 3 kbar and pH 4.6.…”
mentioning
confidence: 99%